COMPARISON OF MOTOR PROFILE OF CHILDREN INSIDE AND OUTSIDE OF APPROPRIATE BODY MASS INDEX (BMI) IN A BASKETBALL PROJECT. (Fiep Bulletin - online, 2013)
It is observed that the motor development constitutes one of the most important research fields in the area of physical education with applied research in various fields of professional practice. In the pediatric population, the study of motor development through sports is fundamental, because it is during this period that children acquire motor experience to enjoy them into adulthood and become physically active. The article presents a comparison of the profile of children with different body mass index (BMI) involved in University extension project "Basket ball", that develops the initiation to basketball, thus follows a comparative methodology between the pre and post evaluation. The research consisted of 18 girls aged 10 to 14 years. Were applied the following tests: abdominal resistance test; the test of 50 meters; the test of 1000 meters and the Shuttle Run test, besides the jump tests: vertical and horizontal. For BMI using height and weight measurements, (weight/height squared). We analyzed the difference between pre and post evaluation data, both in the IMC as in motor testing, that pointing out the importance of physical activity to maintain a healthy lifestyle in the pre and early teens. School basketball training improved skeletal muscle development, limiting the gain weight healthily as the girls developed and provided improvements in their body movements. The motor profile of the girls between 10 and 14 years has different results when related to BMI. Girls with a BMI above the recommended by the World Health Organization have underperformed of the others from the same age, in both evaluations. Therefore, we were able to analyze and conclude that girls with a BMI in the normal range have better physical fitness than those that are outside the normal range.
Keywords: BMI; fitness; sports initiation